Pleiotropic Anticancer Properties of Scorpion Venom Peptides: Rhopalurus princeps Venom as an Anticancer Agent - Mikaelian AG; Traboulay E; Zhang XM; Yeritsyan E; Pedersen PL; Ko YH; Matalka KZ (Dove Medical Press, 2020)
Arthur G Mikaelian,1 Eric Traboulay,1 Xiaofei Michael Zhang,1 Emma Yeritsyan,2 Peter L Pedersen,3 Young Hee Ko,3 Khalid Z Matalka4 1Medolife Corporation, Beverly Hills, CA, USA; 2Yerevan State Medical University, Yerevan, Armenia; 3Johns Hopkins University, School of Medicine Laboratory, Baltimore, MD, USA; 4OncoTherapeutica, Inc., Cambridge, MA, USACorrespondence: Arthur G Mikaelian 433 North Camden Drive, Beverly Hills, CA 90210, USAEmail artur@medolife.comAbstract: To date, the success of conventional chemotherapy, radiotherapy, and targeted biological therapies in cancer treatment is not satisfactory. The main reasons for such outcomes rely on low target selectivity, primarily in chemo- and radiotherapy, ineffectiveness to metastatic disease, drug resistance, and severe side effects. Although immune checkpoint inhibitors may offer better clinical promise, success is still limited. Since cancer is a complex systemic disease, the need for new therapeutic modalities that can target or block several steps of cancer cell characteristics, modulate or repolarize immune cells, and are less toxic to healthy tissues is essential. Of these promising therapeutic modalities are pleiotropic natural products in which scorpion venom (SV) is an excellent example. SV consists of complex bioactive peptides that are disulfide-rich of different peptides’ length, potent, stable, and exerts various multi-pharmacological actions. SV peptides also contain ion channel inhibitors. These ion channels are dysregulated and overexpressed in cancer cells, and play essential roles in cancer development and invasion, as well as depolarizing immune cells. Furthermore, SV has been found to induce cancer cell apoptosis, and inhibit cancer cells proliferation, invasion, metastasis, and angiogenesis. In the current review, we are presenting data that show the pleiotropic effect of SV against different types of human cancer as well as revealing one potential anticancer agent, Rhopalurus princeps venom. Furthermore, we are addressing what is needed to be done to translate these potential cancer therapeutics to the clinic.Keywords: angiogenesis, apoptosis, cell arrest, cytotoxicity, immunomodulation, ion channels, metastasis, polarization